Implementation of an a Priori theoretical model of mathematical competence associated with the learning of a mathematical object - García-Quiroga, Bernardo; Coronado, Arnulfo; Giraldo-Ospina, Albeiro (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article is the product of a research addressed to support the mathematics teacher with didactic orientations to promote the development of the mathematical competences of the students. In the research work a methodological complementarity was used and specific guidelines of Participatory Action Research were taken on. The a priori theoretical model of mathematical competence was formulated with the contributions of researchers like Bishop, Sfard, D'Amore, Godino, Fandiño and Solar. This model was applied during the first half of 2015 and focused on a sequence of mathematical tasks centred on the current peace process between the Revolutionary Armed Forces of Colombia, FARC, and the Colombian government. The implementation of the model was made with the collaboration of sixth grade students of the Educational Institution Jorge Eliécer Gaitán of Florencia, Caquetá. The a priori theoretical model formulated transcended the cognitive aspect; its application contributed to the development of mathematical processes, affective and action trend processes for sharing and developing mathematical meaning in class. In this way, it was constituted in an adequate didactic mediation that guides the teacher in his / her purpose of developing the mathematical competences of the students.